Моделирование режима рекуперативного торможения в имитационной модели вентильно-индукторного двигателя - Галайко, Лидия Петровна (Одесский национальный политехнический университет, 2017)
Проведено моделирование рекуперативного торможения вентильно-индукторного двигателя рудничного электровоза мощностью 27 кВт и частотой вращения 1146 мин-1 с помощью имитационной модели для программы Simulink пакета программ Matlab. Значение управляющих параметров определялось из механических характеристик, полученных с помощью имитационной модели установившихся режимов. Приведены механические характеристики и графики процессов.

One of applications SRM, requiring the difficult algorithms of management, there is a transport. One of the most problem modes SRM on a transport is mode of the braking. Aim of work : to work out the laws of change parameters for providing of constancy of speed in the mode of the braking and in transition from the mode of engine in the mode of the braking for SRM by means of simulation model in the program Simulink package of softwares of Matlab. Studies are undertaken on example fourphase SRM by power 27 kW, by frequency of rotation of 1215 хв-1, mine electric locomotive projected for a drive on the base of engine of direct-current. As managing parameters the corners of including and disconnecting are chosen. Two variants of methods of change of corners were examined: continuous change of corners on a certain law and eventual increase of corners in certain moments of time. The conducted calculations confirmed the necessity of change of managing parameters for the mode of the braking of SRM. For the change of managing parameters at presence of in the SRM sensor of position of rotor the eventual increase of corners of including and corners of disconnecting is recommended in certain moments of time. For the change of managing parameters in a SRM without the sensor of position of rotor the continuous change of corners is recommended on a certain law. It is recommended for the task of managing parameters to use the mechanical descriptions got by means of simulation model for the set modes. Further perfection of adjusting laws is required for reduction of error in the receipt of set.
Modelling of the recuperative braking working mode in imitating model of the switched reluctance motor
Keywords: электрические машины; вентильно-индукторные машины; режим постоянства скорости; механические характеристики; управляющие параметры; Switched Reluctance Motor; mode of constancy of speed; mechanical descriptions; simulation model; managing parameters